Kisaran Inang Hama Krepes - Suryanti Suryanti; Tri Harjaka (Universitas Gadjah Mada, 2007)
Krepes is an acarina which caused damaged to Auricularia sp. cultivation. The fungi attacked by acarina will be dead and decayed. The host range test were done by inoculating krepes on several edible mushroom and on several stages of cultivated Auricularia sp. The research show that krepes attacks only Auricularia sp., and attack all stages of cultivated Auricularia sp.,